(untitled) (Kriminalističke teme, 2018)
Homicide in Malta is not a common crime. Till the present day there is no academic research that inquires the trends associated with this heinous act. After analysing aspects related to homicide committed between 1970 till the latest in 2018, the paper aims at providing the first findings on homicide trends in the islands of Malta. The findings aim at providing the significant statistical outcomes related to homicide trends particularly in relation to the modus operandi, gender, relationship between the offender and homicide clearance.